The COVID-19 pandemic and physical activity during intermittent fasting, is it safe? A call for action - Addin Akbari, Hesam; Ghram, Amine; Yoosef, Mohammad; Arena, Ross; J Lavie, Carl; Chtourou, Hamdi; Ben Saad, Helmi; Chamari, Karim (Biology of Sport, 2021)
Intermittent fasting (IF) has recently gained popularity, and has been used for centuries in many religious practices. The Ramadan fasting is a mandatory form of IF practiced by millions of healthy adult Muslims globally for a whole lunar month every year. In Islam, the “Sunna” also encourages Muslims to practice IF all along the year (e.g.; two days a week). The 2019-Coronavirus disease (COVID-19) pandemic in the context of Ramadan has raised the question whether fasting is safe practice during the COVID-19 pandemic health crisis, and what would be the healthy lifestyle behaviors while fasting that would minimize the risk of infection. As COVID-19 lacks a specific therapy, IF and physical activity could help promote human immunity and be part of holistic preventive strategy against COVID-19. In this commentary, the authors focus on this dilemma and provide recommendations to the fasting communities for safely practicing physical activity in time of COVID-19 pandemic.